You are stronger than you think : unleash the power to go bigger, go bold, and go beyond what limits you - Osteen, Joel (FaithWords, 2021)
"Joel Osteen encourages you to stand firm when the difficulty is not turning around. When the pressure mounts, when you feel overwhelmed, when the struggle looks too big, or the goal is out of reach, you have to remember that is not your destiny. You are more powerful than you think. You need to see yourself the right way and realize what's already inside you. You were made to outlast the competition, to go further than you thought you could, and live a life beyond what limits you. As you read You Are Stronger than You Think, you will find the power to break the cycle of defeat, the courage to set a new standard for your family, the hope to conquer your fear, and the confidence to accomplish every dream. You will discover that you have more strength, more talent, more determination, and more endurance than you ever imagined"--